Analyzing the Performance of Regional Tax Collection Systems: A Case Study of Samsat Offices - Anastasia D'Ornay (Universitas Muhammadiyah Makassar, 2025)
This study examines the performance of regional tax collection systems by focusing on the operational, administrative, and technological dynamics of Samsat offices in Indonesia. As the primary institutions responsible for administering the Motor Vehicle Tax (PKB), Samsat offices play a crucial role in strengthening regional fiscal capacity and supporting decentralized governance. Despite their strategic importance, variations in service quality, administrative efficiency, and technological readiness persist across regions. This research employs a quantitative approach using surveys distributed to taxpayers and administrative personnel to evaluate key performance dimensions, including service efficiency, digital service adoption, transparency, inter-agency coordination, and taxpayer compliance. Additional secondary data from provincial revenue reports and institutional documents complement the primary dataset. The findings reveal that administrative efficiency and service quality remain central determinants of taxpayer satisfaction and compliance, while digital innovations—such as online tax renewal platforms and mobile Samsat services—significantly improve accessibility and reduce processing times. However, disparities in infrastructure, digital literacy, and organizational readiness hinder uniform implementation across provinces. Inter-agency coordination among Bapenda, POLRI, and insurance providers also influences service consistency and operational effectiveness. Overall, the study demonstrates that enhancing Samsat performance requires integrated strategies combining administrative streamlining, digital transformation, human resource development, and improved governance mechanisms. The results provide practical implications for policymakers seeking to strengthen regional tax administration and contribute to the broader literature on public sector performance and fiscal management.